2017
DOI: 10.1002/jbmr.3172
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Inhibits NF-κB/NFATc1 Signaling and Prevents Osteoclast Precursor Differentiation, In Vitro and In Mice

Abstract: The mechanistic target of rapamycin complex 1 (mTORC1) is a critical sensor for bone homeostasis and bone formation; however, the role of mTORC1 in osteoclast development and the underlying mechanisms have not yet been fully established. Here, we found that mTORC1 activity declined during osteoclast precursors differentiation in vitro and in vivo. We further targeted deletion of Raptor (mTORC1 key component) or Tsc1 (mTORC1 negative regulator) to constitutively inhibit or activate mTORC1 in osteoclast precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 55 publications
7
57
0
Order By: Relevance
“…Two well‐described transcription factors involved in the slow fibre switch program are NFATc1 and MEF2 . Levels of MEF2A and MEF2D are both increased in RAmKO muscle, and NFATc1 has been shown to be negatively regulated by mTORC1 . Yet, in both cases, it is unclear whether mTORC1 directly affects these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Two well‐described transcription factors involved in the slow fibre switch program are NFATc1 and MEF2 . Levels of MEF2A and MEF2D are both increased in RAmKO muscle, and NFATc1 has been shown to be negatively regulated by mTORC1 . Yet, in both cases, it is unclear whether mTORC1 directly affects these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the biological and clinical importance, there are only a few reports on mTORC1 and osteoclastogenesis, including two recent studies presenting conflicting results 36,37 . However, these studies could not provide a unifying explanation for the contradictory clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhang et al deleted Raptor or Tsc1 with LyzM-Cre to inhibit or activate mTORC1 signaling, respectively 37 . In agreement with this study, we observed similar in vivo bone phenotypes as well as ex vivo osteoclast differentiation using LyzM-Cre.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations